Temperature and Structure Dependence of the Flexural Strength and Modulus of Freshwater Model Ice - Gow, Anthony J.; Ueda, Herbert T.; Govoni, John W.; Kalafut, John (1988)
This report presents results of small beam testing conducted in a test tank on ice corresponding in structure to the two major ice types, S1 and S2, encountered in lake ice sheets. Tests of 730 beams in the temperature range -1 to -19 C showed that macrocrystalline (S1) and columnar (S2) ice differ appreciably in their flexural characteristics, and that these differences are attributable to variations in the size and orientation of the crystals in the ice and the thermal condition of the beams. Parallel testing of cantilever and simply-supported beams indicated a virtual non-dependence of flexural strength on the temperature of the fiber in tension. It was also determined that the sharply terminated corners of conventional cantilever beams are a source of appreciable stress concentration that can reduce the intrinsic flexural strength by as much as one-half, but which, in most cases, can be substantially relieved by drilling holes at the beam roots. Overall, flexural strengths did not exceed 1200 kPa for cantilever beams or 1650 kPa for simply supported beams tested in parallel with cantilever beams. The highest flexural strengths were measured on isothermal simply supported beams of S2 ice tested with the top surface in tension, with average strengths for such ice increasing from 1650 kPa at -1 C to nearly 2600 kPa at -19 C. Beams made to fail with bottom in tension tested about 35% weaker because of the greatly increased size of crystals in the bottom of S2 ice sheets. Beams of S1 ice yielded flexural strengths midway between those measured on S2 ice.(EDC)